(untitled) (Revista de Ciências Agroveterinárias, 2019)
Soil organic matter is essential within the agricultural system and its accumulation can be favored by the contribution of vegetal residues on the soil. The objective is to evaluate the effect of the grazing height of Urochloa ruziziensis in levels and stocks of soil organic carbon and nitrogen, in agro-pastoral system, in Distrophic Red Latosol typically. For this study, soil samples were collected between the years 2010 and 2012. The design was on randomized blocks in split plots of time and five treatments, constituted of grazing heights: 10; 20; 30 and 40 cm and one more area without grazing of Urochloa ruziziensis, and three repetitions. It was determined in soil layers (0-10, 10-20 e 20-30 cm depth) the level and stock of total organic carbon, particularly carbon, carbon associated with minerals, level and stock of total nitrogen and content of mineral nitrogen. The variables studied were submitted to variance analysis by the F test and the means were compared by the Tukey test, both at 5% probability level. The levels and stocks of total organic carbon in soil and their fractions, the levels of total nitrogen and mineral soil beyond stocks of total nitrogen soil, were not changed by the grazing heights and the area grazed. However, in the 0-10 cm layers, there was an increase in the contents and total organic carbon, organic carbon associated with the minerals and the reduction of the particulate organic carbon of the soil, as well as the increase of the total nitrogen contents between the first and second year of driving, under no-tillage. There was an increase of mineral nitrogen after the soybean harvest to all layers of the soil.